Jejak C. Snouck Hurgronje di Kesultanan Cirebon: Studi Atas Surat-Surat Sultan Sepuh XI (Djamaloedin Aloeda) untuk Snouck Hurgronje dalam Kurun 1908-1912 - Irfanullah, Gumilar; Anggraeni, Dewi; Sya'ban, Ginanjar (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
This study aims to analyse the relationship between Sultan Sepuh XI, Djamaloedin Aloeda of Kasepuhan and colonial advisor Christiaan Snouck Hurgronje in the early 20th century in the Dutch East Indies. This study is primarily concerned with the analysis and philological study of a series of letters written by Djamaloedin Aloeda to Snouck during the period between 1908 and 1912. Aloeda was the Sultan of the Kasepuhan Cirebon Palace, succeeding his mother, Ratu Adima, who died in 1918. This research employs a historical approach to explore the historical data and evidence drawn from the letters, with the aim of providing a broader and more detailed picture of the historical narrative and the pattern of relations between the two parties. The research identified that the relationship between Snouck and Aloeda was characterised by a familial bond based on the marital ties of their relatives. This relationship demonstrated that royal status, such as the title of Sultan in Kasepuhan, was attained through close ties and the approval of the Dutch colonial government.